2022
DOI: 10.1016/j.thromres.2021.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Sustained inflammation, coagulation activation and elevated endothelin-1 levels without macrovascular dysfunction at 3 months after COVID-19

Abstract: Introduction Endothelial damage and thrombosis caused by COVID-19 may imperil cardiovascular health. More than a year since the WHO declared COVID-19 pandemic, information on its effects beyond the acute phase is lacking. We investigate endothelial dysfunction, coagulation and inflammation, 3 months post-COVID-19. Materials and methods A cohort study was conducted including 203 patients with prior COVID-19. Macrovascular dysfunction was assessed by measuring the carotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 51 publications
5
58
0
6
Order By: Relevance
“…Our results are replicated by Willems et al who reported an elevation in ET-1 levels for a subset of 36 Covid-19 infected patients during the acute illness compared with a historic non-infected control group [12]. Gregoriano et al had earlier reported on the lack of prognostic utility of C-terminal proendothelin-1 (proET-1) to predict mortality in Covid-19 [14].…”
Section: Gr Abraham Et Alsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results are replicated by Willems et al who reported an elevation in ET-1 levels for a subset of 36 Covid-19 infected patients during the acute illness compared with a historic non-infected control group [12]. Gregoriano et al had earlier reported on the lack of prognostic utility of C-terminal proendothelin-1 (proET-1) to predict mortality in Covid-19 [14].…”
Section: Gr Abraham Et Alsupporting
confidence: 83%
“…Willems et al have recently reported elevated ET-1 levels in patients 3 months post Covid-19 infection [12]; however the association of ET-1 with clinical outcomes likely to impact the provision of healthcare resources, such as hospitalisation, has not been investigated. In the present study, we tested the hypothesis that elevated levels of plasma ET-1 in the acute phase of Covid-19 infection would be associated with more severe disease.…”
Section: Introductionmentioning
confidence: 99%
“…EDN1 (Endothelin-1) has been considered a neuroprotective factor that participates in the olfactory response modulation through the uncoupling of gap junctions ( 87 , 88 ). Interestingly, elevated EDN1 levels together with a sustained inflammation has been observed 3 months after recovery from acute COVID-19 symptoms ( 89 ). SPP1 (osteopontin) participates in the OB synaptic plasticity ( 90 ) and acts as a molecular brake regulating neuroinflammatory response to chronic viral infections ( 91 ).…”
Section: Resultsmentioning
confidence: 99%
“…EDN1 (Endothelin-1) has been considered a neuroprotective factor that participates in the olfactory response modulation through the uncoupling of gap junctions (Le Bourhis et al, 2014;Bryche et al, 2019). Interestingly, elevated EDN1 levels together with a sustained inflammation has been observed 3 months after recovery from acute COVID-19 symptoms (Willems et al, 2021). SPP1 (osteopontin) participates in the OB synaptic plasticity (Powell et al, 2019) and acts as a molecular brake regulating neuroinflammatory response to chronic viral infections (Mahmud et al, 2020).…”
Section: Resultsmentioning
confidence: 99%